2020
DOI: 10.3390/en13092273
|View full text |Cite|
|
Sign up to set email alerts
|

The Causal Connection of Natural Resources and Globalization with Energy Consumption in Top Asian Countries: Evidence from a Nonparametric Causality-in-Quantile Approach

Abstract: Given the significance of energy conservation as a prime objective of environmental sustainability, countries all around the world are keen to identify significant factors that lead to the augmentation of energy utilization. Considering the rising emphasis of economies in utilizing natural resources to attain higher levels of globalization, the current research was aimed at investigating how the returns of natural resources and globalization affect energy consumption in top Asian economies. In doing so, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Furthermore, the literature shows that the process of globalization significantly drivers carbon emissions. Although several scholars widely study the influence of globalization on carbon emissions but they still do not reach any consensus about the specific role of globalization on CO 2 emissions such as Shahbaz et al (2018); Sethi et al (2020); Hussain et al (2020) studied the influence of globalization on environmental sustainability and reported that globalization could degrade the environmental quality in a various contextual setting. On the other hand, Shahbaz et al (2017); Balsalobre‐Lorente et al (2020) investigated that globalization process significantly enhances environmental quality in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the literature shows that the process of globalization significantly drivers carbon emissions. Although several scholars widely study the influence of globalization on carbon emissions but they still do not reach any consensus about the specific role of globalization on CO 2 emissions such as Shahbaz et al (2018); Sethi et al (2020); Hussain et al (2020) studied the influence of globalization on environmental sustainability and reported that globalization could degrade the environmental quality in a various contextual setting. On the other hand, Shahbaz et al (2017); Balsalobre‐Lorente et al (2020) investigated that globalization process significantly enhances environmental quality in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…In order to use non-parametric estimation techniques, several elements are of critical importance, like bandwidth choice (Hussain et al, 2020). Its importance lies in its ability to identify the neighborhood size around the target point, which ensures the smoothness of estimates.…”
Section: Methodsmentioning
confidence: 99%
“…--------------::::::::::::::::::::::::::::::::::: ----------------------------::::::::::::::--------------------------COS 25 5.17 GDP per capita (current LCU), and GDP per capita (current US$) with the average trends of 1.10E+05 and 3219.47 in US dollars and deviation of 47393 and 1482 respectively (Hussain et al, 2020;.…”
Section: Ctrmentioning
confidence: 99%